2005
DOI: 10.1111/j.1365-2672.2005.02601.x
|View full text |Cite
|
Sign up to set email alerts
|

Contact inactivation of orthopoxviruses by household disinfectants

Abstract: Aims: The aim of this study is to identify common household disinfectants that combine significant activity against the type orthopoxvirus, vaccinia virus with minimal impact in terms of potential toxicity and/or damage to household or personal items. Methods and Results: Laboratory scale experiments assessed common disinfectants containing anionic and nonionic detergents, oxygen-based bleach, potassium peroxomonosulfate, chloroxylenol or halogenated phenols. Disinfectants were assessed for their ability to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 11 publications
0
24
0
Order By: Relevance
“…9 Other Studies have also shown that most frequently used fomites are most likely to be contaminated and consequently they will generally carry heterotrophic bacterial loads. 10 However, this study has observed that most common bacterial contaminants at Daeyang Luke Hospital just like any other hospital in the developing world are S. aureus, E. coli and P. aeruginosa.…”
Section: Resultsmentioning
confidence: 99%
“…9 Other Studies have also shown that most frequently used fomites are most likely to be contaminated and consequently they will generally carry heterotrophic bacterial loads. 10 However, this study has observed that most common bacterial contaminants at Daeyang Luke Hospital just like any other hospital in the developing world are S. aureus, E. coli and P. aeruginosa.…”
Section: Resultsmentioning
confidence: 99%
“…transmitting microbial germs from one person to another (1,2). This is especially important in health centers because the constant handling of the mobile phones by hospital staffs facilitates gathering various types of nosocomial germs that can become an important source for transmission of these infections (3). In fact, the use of mobile phone by clinical staffs can enhance pathogen transmission and might intensify the hardship of interrupting infection spread (4).…”
Section: Introductionmentioning
confidence: 99%
“…Cultures were incubated for 24 h post-infection (p.i.) to ensure maximum yield of progeny in untreated cultures, after which the released virus was titrated by TCID 50 assay (Butcher & Ulaeto, 2005). All three inhibitors resulted in a significant decrease in yield, with 2-DG and OX causing .3 log drop in virus yield, whereas LON caused a 1 log drop (Fig.…”
mentioning
confidence: 99%